2018
DOI: 10.1172/jci97325
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase USP9X regulates FBW7 stability and suppresses colorectal cancer

Abstract: The tumor suppressor FBW7 targets oncoproteins such as c-MYC for ubiquitylation and is mutated in several human cancers. We noted that in a substantial percentage of colon cancers, FBW7 protein is undetectable despite the presence of FBW7 mRNA. To understand the molecular mechanism of FBW7 regulation in these cancers, we employed proteomics and identified the deubiquitinase (DUB) USP9X as an FBW7 interactor. USP9X antagonized FBW7 ubiquitylation, and Usp9x deletion caused Fbw7 destabilization. Mice lacking Usp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 43 publications
2
62
0
Order By: Relevance
“…In addition, USP9X and USP13 have been reported to deubiquitinate MCL1 for stabilization (10,11). However, USP9X exhibits tissue-specific expression primarily in the brain and immune system (12), and sometimes functions as a tumor suppressor in certain biological processes and malignancies (13,14). Similarly, USP13 acts as a tumor suppressor by stabilizing PTEN expression in breast cancer (15).…”
mentioning
confidence: 99%
“…In addition, USP9X and USP13 have been reported to deubiquitinate MCL1 for stabilization (10,11). However, USP9X exhibits tissue-specific expression primarily in the brain and immune system (12), and sometimes functions as a tumor suppressor in certain biological processes and malignancies (13,14). Similarly, USP13 acts as a tumor suppressor by stabilizing PTEN expression in breast cancer (15).…”
mentioning
confidence: 99%
“…26,36,[38][39][40][41][42][43] Conversely, USP9X has tumor suppressor functions in pancreatic ductal adenocarcinoma 37,44,45 and colorectal cancer. 46 Interestingly, 2 recent studies showed that USP9X stabilizes large tumor suppressor kinase 2, an upstream component of the Hippo pathway, to negatively regulate YAP and its target genes to suppress tumor growth in pancreatic 44,45 and breast 44 cancer. In contrast, another study reported that USP9X deubiquitinates and stabilizes YAP1, a major downstream effector of the Hippo pathway, thus promoting breast cancer cell survival and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…The function of USP9x is cell-type specific. USP9x has been viewed as a tumor suppressor gene in colorectal and pancreatic ductal adenocarcinoma, while others reported that USP9x is an oncogene in breast cancer, glioblastoma, and leukemia (Akiyama et al, 2019;Chen et al, 2019;Khan et al, 2018a;Pal et al, 2018;Potu et al, 2017b;Zhu et al, 2018). Our results suggest that USP9x may function as an oncoprotein through regulating SOX2 in osteosarcoma.…”
Section: Many Transcription Factors Have Been Involved In the Pathogementioning
confidence: 99%